Income and Markers of Immunological Cellular Aging. Issue 6 (July 2016) - Aiello, Allison E.; Feinstein, Lydia; Dowd, Jennifer B.; Pawelec, Graham; Derhovanessian, Evelyna; Galea, Sandro; Uddin, Monica; Wildman, Derek E.; Simanek, Amanda M.
ABSTRACT: Objective: Socioeconomic disadvantage may contribute to poor health through immune-related biological mechanisms. We examined the associations between socioeconomic status, as measured by annual household income, and T-cell markers of aging, including the ratios of CD4 and CD8 effector cells to naïve cells (E/N ratio) and the CD4/CD8 T-cell ratio. We hypothesized that participants with a lower income would have higher E/N ratios and lower CD4/CD8 ratios compared with participants with a higher income, and that these associations would be partially mediated by elevated cytomegalovirus (CMV) IgG antibody levels, a virus implicated in aging and clonal expansion of T cells. Methods: Data were from 79 individuals who participated in the population-based Detroit Neighborhood Health Study. We used linear regression to quantify the association between a 10, 000 decrease in income and each ratio outcome. Results: After adjustment for age, sex, race, smoking, medication use, and lifetime history of mental health conditions, lower income was associated with a 0.41 (95% confidence interval = 0.09–0.72) log-unit increase in the CD4 E/N ratio and a 0.20 (95% confidence interval = 0.02–0.39) log-unit increase in the CD8 E/N ratio. CMV immunoglobulin G antibody level partially mediated these associations. Conclusions: Our study suggests that low socioeconomic status is associated with immunological aging as measured by the E/N ratio and that impaired immune control of CMV may partially mediate these associations. Abstract : Supplemental digital content is available in the text.